MOSFET noise modeling for wireless applications - Chen, Xuezhong. (2008)
This thesis presents a high-frequency noise model of MOS (Metal Oxide Semiconductor) devices. The high frequency (HF) noise model is based on the equivalent circuit of the MOS device, but it takes into account both the gate resistance distribution and hot carrier effect.